La biología molecular como herramienta de ayuda en la clasificación de los taxones en el orden primates (2021)
This work is one of the many investigations that have been carried out on the role that Molecular Biology has played in determining the phylogenetic relationships that exist between different groups of organisms. Through the compilation of multiple studies and a comparative analysis, the aim is to establish the usefulness of Molecular Biology as a determining tool in solving the different taxonomic problems in the phylogenetic relationships of the Order Primates. The objective of each of the chapters is to highlight some of the most important examples in which Molecular Biology has functioned as a buffer for the solution of some of the deepest phylogenetic problems in this order of mammals. We will deal with topics such as the previous classification of the Order Chyroptera (Bats) as a sister group of Primates and the new regrouping of these orders with respect to Rodents.